Distributed coordination control of hybrid energy resources for power sharing in coupled hybrid DC/AC microgrid using paralleled IFCs/ILCs. Issue 1 (24th January 2019) - Agrawal, Alok; Gupta, Rajesh
Abstract : This study proposes flexible controllers for the interlinking converter (ILC) and interfacing converters (IFCs) used in coupled hybrid AC/DC microgrids (HMGs). Proposed controllers are specifically designed for the multiple stacked bidirectional DC–AC ILCs/IFCs based microgrid outlays, to omit the droop power flow and system stability issues. The ILC and IFC grid supportive converter controllers focus on the wide‐spread AC/DC bus parameters control for both DC and AC bus voltage regulation and superfluous power sharing while operating in the grid forming and feeding modes. Proposed controllers minimise the need for the controller parameter tuning as opposed to the conventional controllers used in zonal HMG systems. This makes the system stable for a much wider operating conditions as opposed to the widely used higher‐order PLL integrated PQ and dq 0 control algorithms. The proposed HMG also integrates the centralised battery energy stack through bidirectional dual active bridge DC–DC converter for achieving the high‐power transfer efficiency and omitting the isolation issues between medium‐voltage and low‐voltage DC buses. The HMG system performance is evaluated using the simulation studies for various strategical operational modes. Further, the proposed controllers have also been tested individually on experimental platform.